The impact of temperature on heterocathode noise diodes characteristics - Botsula, O. V.; Prykhodko, K. H.; Zozulia, V. O. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2024)
Background. The creation of compact noise sources in a wide frequency range, capable of invariance and reproducibility characteristics over time and external conditions, is an urgent task in the telecommunications and security field, in particular, as reference signal sources for measuring the noise characteristics of amplifiers and receivers. One of the devices that can satisfy the requirements for noise sources are diodes with a cathode static domain (DCSD). An important factor that affects the characteristics of semiconductor devices is temperature and self-heating.Purpose of Work. The aim of the work is to study the effect of temperature and self-heating on the characteristics of DCSDs containing a graded-band layer based on nitride compounds.Techniques and Methodology. Diode characteristics are obtained by numerical modeling of carrier transfer processes in two-dimensional semiconductor structures using the ensemble Monte Carlo method. Substantial mechanisms of scattering of charge carriers are taken into account. The work calculates the dependences of the current density on different values of the constant bias voltage on the diode and on different temperatures with and without taking into account heating. The phonon model was used to describe the heating processes in the selected diodes.Results. The dependences of the current density on the applied supply voltage were obtained for various DCSD doioded with a graded band AlGaN cathode under the conditions of a different constant temperature and taking into account the of self-heating effects. It is shown that an increase in temperature leads to a decrease in the diode current density. The self-heating effect is shown can significantly limite the operating voltage range of the diode.Conclusions: The effect of temperature on the operation of diodes based on AlGaN with a graded gap heterocathode is demonstrated. An increase in temperature leads to a limitation of the working voltages of the diode and, under the conditions of impact ionization, can lead to the destruction of the diode.